Eksplorasi Material Tisu Kering dan Lem Latex sebagai Prostetik Alternatif dalam Pengembangan Rias Fantasi Bertema Akar Alami - Marta Kristina S; Taofan Ali Achmadi (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
This study aims to develop a fantasy makeup concept with a natural root theme through the exploration of dry tissue and latex glue as alternative prosthetic materials. This research is a Research and Development (R&D) study using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. Product development in this study focused on the exploration of dry tissue and latex glue as alternative media in creating root-themed fantasy makeup. Validation was conducted by three makeup experts using a Likert scale instrument from 1-5, covering aspects of visual aesthetics, elements and principles of fine art, product creativity, and element application techniques. Data were analyzed descriptively and quantitatively using a feasibility percentage formula. The results showed an achievement level of 88.48%, which is included in the "Good" category. These findings indicate that simple materials such as dry tissue and latex glue have the potential to be an economical and applicable alternative prosthetic material in fantasy makeup learning.